비용편익분석을 위한 조건부가치측정법에서의 총편익 산정: 소득효과 및 거리-소멸 효과를 중심으로 - 이종연 (13565, 2014)
This study suggests a model for calculating total benefit rigorously to use the contingent valuation method (CVM) in cost-benefit analysis (CBA). Estimating households’ willingness to pay through survey method, the study attempts to demonstrate if a resp